2014
DOI: 10.1167/iovs.14-15133
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Production and Antigen Recognition by Human Mucosal Homing Conjunctival Effector Memory CD8+ T Cells

Abstract: These data demonstrate that the majority of conjunctival epithelial CD8(+) T cells are mucosal homing αEβ7(+) effector memory T cells, which can recognize viral epitopes and are capable of secreting Granzyme B and IFN-γ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Using immunohistochemistry on conjunctival biopsies, the involvement of CD4 + and CD8 + T cells in Sjogren and non-Sjogren DED patients has been reported3839. More recently, impression cytology has been used to demonstrate the preponderance of mucosal-homing CD8 + T EM cells in the conjunctiva of healthy individuals40.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using immunohistochemistry on conjunctival biopsies, the involvement of CD4 + and CD8 + T cells in Sjogren and non-Sjogren DED patients has been reported3839. More recently, impression cytology has been used to demonstrate the preponderance of mucosal-homing CD8 + T EM cells in the conjunctiva of healthy individuals40.…”
Section: Discussionmentioning
confidence: 99%
“…Although these are relatively non-invasive, they may show a predisposition towards more superficial intraepithelial T cells as opposed to stromal cells and follicular T cells, and therefore do not represent the entire T cell population in the ocular surface mucosa. However, impression cytology is a standard procedure used in various studies of ocular surface disease1340.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst CD3 + T cells, effector memory T cells predominate in the human ocular surface. In earlier experiments, it has also been shown that CD8 + memory cells are the major populations in the conjunctival epithelial T cells among the healthy individuals 20 . Figure 3 shows that CD4 + and CD8 + effector memory T cells (T EM and T EMRA ) are the major subset in the human ocular surface in 10 healthy controls studied.…”
Section: Representative Resultsmentioning
confidence: 91%
“…The compensation was performed by testing PBMCs initially according to the protocol mentioned in Williams et al . 20 For testing, PBMCs were incubated with the same set of antibodies used here and compensated by comparing single and multiple antibody stains.…”
Section: Protocolmentioning
confidence: 99%
“…Ocular surface impression cytology is a simple minimally invasive test currently used in clinical practice for the diagnosis of limbal epithelial stem cell failure. 13 When adhered cells are recovered and analyzed by multicolor flow cytometry (OSIC-flow), 14 16 the technique provides a means to characterize the ocular mucosal cellular response associated with progressive conjunctival fibrosis and identify cellular subsets that may be associated with disease activity and progressive fibrosis when clinical evidence of inflammation has subsided.…”
mentioning
confidence: 99%